Analisis Pengaruh Kualitas Produk dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Sambal Gami Jeet 81 Porong: Analisis Pengaruh Kualitas Produk Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Sambal Gami Jeet 81 Porong - Nur Fadilah_ Nur Fadilah; Afifatus Sholikhah (Universitas Nahdlatul Ulama Sidoarjo, 2024)
This research aims to assess the influence of Product Quality and Service Quality on Customer Satisfaction at Sambal Gami Jet 81 Porong. Data was collected using a survey method from 44 respondents who are loyal customers of Sambal Gami Jet 81. The data was then analyzed using multiple linear regression analysis. The research results show that Product Quality and Service Quality significantly influence Customer Satisfaction. This research highlights the importance of prioritizing and improving Product Quality and Service Quality to maintain and increase customer satisfaction in food businesses such as Sambal Gami Jet 81 Porong.